2021
DOI: 10.3389/fpsyg.2020.612565
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Mediation Paths Linking Corporate Social Responsibility to Employee’s Job Performance: A Multilevel Approach

Abstract: This study attempts to examine the direct impact of corporate social responsibility (CSR) initiatives on employees’ job performance and the indirect relationships between CSR initiatives on employees’ job performance via industrial relations climate and psychological contract fulfillment. Data were collected from 764 supervisor–subordinate dyads and 271 middle managers from 85 companies. Using a multilevel approach, the results showed that organizational-level CSR was positively related to employees’ job perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Our study emphasizes the importance of relational outcomes in evaluating the overall success of internal CSR programs. Although prior research has extensively examined mediators between CSR and individual outcomes (e.g., Farooq et al, 2014 ; Fang et al, 2021 ; Yan et al, 2021 ), none of them has considered the mediating mechanism through employees’ perceived CA. By introducing perceived CA as a mediator, our study explores a new underlying mechanism through which employees’ CSR perceptions could influence their relational outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our study emphasizes the importance of relational outcomes in evaluating the overall success of internal CSR programs. Although prior research has extensively examined mediators between CSR and individual outcomes (e.g., Farooq et al, 2014 ; Fang et al, 2021 ; Yan et al, 2021 ), none of them has considered the mediating mechanism through employees’ perceived CA. By introducing perceived CA as a mediator, our study explores a new underlying mechanism through which employees’ CSR perceptions could influence their relational outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… Zhao et al (2019) surveyed Chinese employees and indicated that employees’ CSR perceptions were positively associated with their organizational identification. Fang et al (2021) surveyed employees across different industries in China and concluded that employees’ CSR perceptions were positively associated with their job performance and such effect was mediated by industrial relations climate and psychological contract fulfillment. Yan et al (2021) found that employees’ CSR perceptions were positively associated with employees’ behaviors to challenge the company’s status quo.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of external stakeholders, some scholars have explored the influence mechanism of corporate social responsibility on corporate financial performance (Waddock and Graves, 1997), consumers (Luo and Bhattacharya, 2006) and corporate reputation (Johnson, 2003). Although some scholars have initially explored the positive correlation between corporate social responsibility and employee turnover rate based on the social identity theory (Ng et al, 2019), they have not explored the impact path of corporate social responsibility on employee turnover intention based on the level of employees as an internal interest group (Chen and Donna, 2020;Fang et al, 2021). This led to the research on the underlying mechanism of employee perception of corporate social responsibility is still "fragmented and incomplete" (Gond et al, 2017).…”
Section: Introductionmentioning
confidence: 99%